Steroid‐Induced Psychosis in a Child With Nephrotic Syndrome Secondary to Focal Segmental Glomerulosclerosis: A Case Report - Sushan Pokharel; Amrit Bhusal; Himal Bikram Bhattarai; Tek Nath Yogi; Prabha Bhandari; Deepti Pandit (Clinical Case Reports)
ABSTRACT Corticosteroid‐induced psychosis is rare and less reported in children compared to adults. However, psychosis is considered a severe adverse effect of corticosteroids in pediatric nephrotic syndrome. Steroid‐induced psychosis is dose‐dependent and should be treated by tapering the dose of steroids and usually initiating an atypical antipsychotic. A 13‐year‐old male child presented to the pediatrics outpatient department with complaints of anxiety, fearfulness, and seeing images of an old man crawling into his room and threatening to strangle him with a red rope, which led to decreased sleep. He was initiated on oral prednisolone 3 weeks ago after being diagnosed with nephrotic syndrome. A diagnosis of steroid‐induced psychosis was made, and he was tapered on steroids over 6 weeks. He was then initiated on tacrolimus, quetiapine, and lorazepam and was discharged after a week. At follow‐up in 4 weeks, his psychosis had resolved, and nephrotic syndrome was found to improve. Children on steroids should be closely monitored for psychotic symptoms over a prolonged duration. Although tapering the dose of steroids is the gold standard treatment of steroid‐induced psychosis, cases like nephrotic syndrome demand the continuous use of an immunosuppressant. In such cases, tacrolimus has been found to be an effective alternative, although continuous monitoring for nephrotoxicity is necessary. Similarly, atypical antipsychotics (like quetiapine) are preferred for psychosis because of their lesser risk for extrapyramidal side effects compared to typicals. Parental counseling and informed consent are utmost for children on steroids or tacrolimus.